Pelaksanaan Protokol Kesehatan Terhadap Pengelolaan Berkas Rekam Medis Di Puskesmas - Hendra Rohman (JURNAL ILMU KESEHATAN BHAKTI SETYA MEDIKA, 2021)
Health protocols are rules and regulations need followed by related parties in order to carry out activities safely during COVID-19 pandemic. Health Protocol is established so people can continue to carry out their activities safely and do not endanger safety or health of others. This study aims to identify health protocol flow implementation on medical record document management at Sewon I and II Health Centers, Bantul Yogyakarta. Qualitative descriptive research method. Interviews were conducted with filling officers. Result, health protocol implementation flow at Sewon I and II Health Centers has been implemented and carried out by all relevant parties. Officers use personal protective equipment, namely masks, gowns, handscoons, face shields, and headscaps. Medical record document management by drying and spraying after service. Conclusion, health protocol flow needs to implemented by all officers. Medical record document management during covid-19 pandemic needs adjustments to circulars from professional organizations. SOPs related to health protocols have been listed in policy for medical records organizing.